Development of Sensory Board Media in Rhythm Relay Activities to Stimulate Sensorimotor Skills in Early Childhood - Juniarti, Yenti; Sutisna, Icam; Fitriana, Fitriana; Lestari, Dwi Puji; Anggraini, Denok Dwi; Ramadan, Gilang (Universitas Pendidikan Indonesia Kampus Serang, 2025)
Although various theories emphasize the importance of sensorimotor activities in child development, the application of concrete media, such as sensory boards, in Montessori learning remains limited. Therefore, this study aims to develop and explore the use of sensory board media to enhance the sensorimotor skills of children in Montessori kindergartens. This research follows a Research and Development (RD) approach involving ten stages of Borg Gall’s educational research and development that the results are summarized in three key results, namely need assessment, development stage, model feasibility and product trial. The instruments used in this study included questionnaires and expert validation sheets. The findings of this study indicate the urgency of developing media that support rhythm relay activities. The results uncovered that the developed sensory board media is highly suitable for use in Montessori learning. The media expert provided a score of 89%, and the content expert rated it at 89.6%. Meanwhile, small-group testing yielded a score of 87.5%, and large-group testing resulted in 88.5%. The study suggests that sensory boards can effectively support sensorimotor development in early childhood students, and further dissemination of sensory board media in rhythm relay activities can further stimulate sensorimotor skills in early childhood.